Unbalanced Feature Identification of Rotor System Based on Fused Cross-Correlation Fast Fourier Transform - Yiheng Sheng; Zinan Wang; Peng Zhou; Zhan Wang; Qian Wang; Siqi Niu (International Journal of Aerospace Engineering)
Rotor system unbalance is one of the most important factors that affects the operating accuracy and stability in aerospace engineering. The extraction and identification of unbalanced features is the premise for the dynamic balance of rotor system. In order to accurately identify the unbalanced vibration feature, based on the fused cross-correlation fast Fourier transform (FC-CFFT) method, an unbalanced feature extraction method of the rotor system is proposed. The convolution window weighs the data of the vibration sequence and carries out delay processing. Through spectrum calculation, the phase information of the vibration signal is obtained. And the amplitude information of the vibration feature can be acquired through cross-correlation calculation. The unbalanced features of the rotor system vibration signals are identified under different working conditions through simulation and experiment. The results show that this method is more accurate than FFT, the cross-power method, and the sine-approximation method in extracting different unbalanced vibration features of the rotor system. The extraction accuracy of unbalanced feature phase and amplitude reaches 98.61% and 97.27%, respectively. After the unbalanced feature is extracted, the dynamic balance experiment can be carried out. The unbalanced feature is used for dynamic balance compensation. In this way, the average amplitude decreased by 76.35%. The high accuracy of the FC-CFFT method for extracting the unbalanced feature has been verified. This research provides a theoretical foundation for the vibration signal processing and dynamic balance control of the rotor system.